Family evaluation of children and adolescents submitted to gastrostomy - Camila Casagrande Mela; Clara Ferraz Lazarini Zacarin; Giselle Dupas (Universidade Federal de Goias, 2015)
The study aimed to understand the structure, operation and development families, to identify social support networks for the care of the child and adolescent submitted to gastrostomy, and to describe difficulties and facilities faced in this experience. We used the Calgary Family Assessment Model as theoretical reference, we added it to the semi-structured interview as research instrument; and we used Narrative Analysis as method. The uses of the technological device affect caregivers and their routines, and establish a relationship of renounce and donation with the gastrectomy patient. Difficulty was found to accept that their children are not fed normally. The main setbacks referred to the lack of knowledge and training for specific homecare. Support is limited. This study allowed better comprehension of experiences from families and showed that the use of a technological device brings benefits to the child's health, thus, it is a difficult process to be accepted at first.